Identification and Functional Characterization of Monofunctional ent-Copalyl Diphosphate and ent-Kaurene Synthases in White Spruce Reveal Different Patterns for Diterpene Synthase Evolution for Primary and Secondary Metabolism in Gymnosperms(1)([W])([OA]) - Keeling, Christopher I. (American Society of Plant Biologists, 2010)
The biosynthesis of the tetracyclic diterpene ent-kaurene is a critical step in the general (primary) metabolism of gibberellin hormones. ent-Kaurene is formed by a two-step cyclization of geranylgeranyl diphosphate via the intermediate ent-copalyl diphosphate. In a lower land plant, the moss Physcomitrella patens, a single bifunctional diterpene synthase (diTPS) catalyzes both steps. In contrast, in angiosperms, the two consecutive cyclizations are catalyzed by two distinct monofunctional enzymes, ent-copalyl diphosphate synthase (CPS) and ent-kaurene synthase (KS). The enzyme, or enzymes, responsible for ent-kaurene biosynthesis in gymnosperms has been elusive. However, several bifunctional diTPS of specialized (secondary) metabolism have previously been characterized in gymnosperms, and all known diTPSs for resin acid biosynthesis in conifers are bifunctional. To further understand the evolution of ent-kaurene biosynthesis as well as the evolution of general and specialized diterpenoid metabolisms in gymnosperms, we set out to determine whether conifers use a single bifunctional diTPS or two monofunctional diTPSs in the ent-kaurene pathway. Using a combination of expressed sequence tag, full-length cDNA, genomic DNA, and targeted bacterial artificial chromosome sequencing, we identified two candidate CPS and KS genes from white spruce (Picea glauca) and their orthologs in Sitka spruce (Picea sitchensis). Functional characterization of the recombinant enzymes established that ent-kaurene biosynthesis in white spruce is catalyzed by two monofunctional diTPSs, PgCPS and PgKS. Comparative analysis of gene structures and enzyme functions highlights the molecular evolution of these diTPSs as conserved between gymnosperms and angiosperms. In contrast, diTPSs for specialized metabolism have evolved differently in angiosperms and gymnosperms.